2020
DOI: 10.3390/su12187826
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Mass and Night Ventilation in Decreasing Cooling Load Demand

Abstract: The building sector consumes 36% of the world’s energy and produces around 40% of energy-related carbon emissions. While the building industry moves towards a zero net greenhouse-gas emission policy, ventilation is, and will be, a necessity for the preservation of air quality—especially in climates defined by unsavoury conditions. Therefore, a “mixing mode” cooling system was employed to lower the required energy consumption at an earthen building situated in the premises of Istanbul Technical University. A ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Results showed that night ventilation via the extractor fan decreased the average daily energy consumption of the mechanical cooling system by an average of 15-27%. Moreover, M. Darmanis et al (2020) stressed that integrating both passive and mechanical cooling systems within buildings, referred to as "mixing mode" cooling systems, can decrease the overall carbon footprint of such buildings [24].…”
Section: Natural Ventilationmentioning
confidence: 99%
“…Results showed that night ventilation via the extractor fan decreased the average daily energy consumption of the mechanical cooling system by an average of 15-27%. Moreover, M. Darmanis et al (2020) stressed that integrating both passive and mechanical cooling systems within buildings, referred to as "mixing mode" cooling systems, can decrease the overall carbon footprint of such buildings [24].…”
Section: Natural Ventilationmentioning
confidence: 99%
“…Passive cooling can be achieved using techniques for solar and heat control, heat amortization and heat dissipation [2]. These techniques can be related to performance in terms of thermal mass, thermal insulation, shading of glazed openings, control of solar radiation, surface thermal properties or air infiltration [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to improve the indoor air quality and, to avoid high concentrations of harmful substances, it is needed to have good ventilation in the house ( Chen Ren, 2019 ; Garcia-Chevesich, 2014 ; Ogen, 2020 ; World Health Organization, WHO Air quality guidelines for particulate matter, ozone, nitrogen dioxide and sulfur dioxide: Global update 2005, 2005 ; World Health Organization, Statement on the second meeting of the Emergency Committee of the International Health Regulations (2005) on the novel coronavirus outbreak (2019-nCoV)., 2020c ). Furthermore, the presence of people in a closed space for a number of hours higher than the usual may imply an increase in the concentration of CO 2 in our rooms ( Balocco, 2020 ; De Gaetani, 2020 ; Darmanis, 2020 ; Dudzik, 2020 ; Hye-Sun Jin, 2020 ; Lee, 2020 ; Rossi, 2020 ; Yao, 2020 ). Electronic devices, known as e-noses, may be conveniently used as smart devices to monitor indoor air quality in a living environment ( Sironi, 2014 ; Viccione D. S., 2014 ; Viccione T. Z., 2012 ).…”
Section: Introductionmentioning
confidence: 99%